EPR and Optical absorption studies of Na2O-Al2O3- B2O3-CuO glasses. (2018) - Ashok, B.; Ramadevudu, G.; Narasimha Chary, M.; Shareefuddin, Md.
Abstract: Alkali borate glasses are promising materials having applications in solid state batteries, fuel cells etc. These glasses are little hygroscopic due to the presence of alkali content. The addition of Al2O3 makes these glasses resistant to alkali oxides. Al2O3 depending upon its concentration in the glass matrix acts as network modifier or glass former. Hence an attempt is made to prepare the glasses of the composition (30-x) Na2 O-xAl2 O3 -69B2 O3 -1CuO by varying Al2 O3 by 0, 5, 10 & 15 mole % replacing equal amounts of Na2O. Glasses are prepared by conventional melt quenching method. X-ray diffractograms are recorded at room temperature. Peak-free X-ray diffractograms confirmed the amorphous nature of these glass samples. Electron Paramagnetic Resonance (EPR) and Optical absorption studies were carried out on Na2 O-Al2 O3 -B2 O3 glasses using Cu 2+ as spin probe. From the EPR Spectra spin-Hamiltonian parameters were evaluated. It was observed that ( ( ∼ 2.33 )> > > g e ( = 2.0023 ) and > > . . From the above results it was concluded that the ground state of Cu2+ orbital is (2_(B_1g)) state and the site symmetry around the Cu 2+ is tetragonally distorted Octahedral. The optical absorption spectra revealed a broad absorption band which is assigned to 2 B 1 g → 2 B 2 g transition. By correlating EPR and Optical data bonding coefficients α 2, β 2, wereevaluated . were evaluated.